Analysis of Tax Understanding, Tax System, and Tax Sanctions on Tax Evasion - Ahmad Bukhori Muslim; Dian Sulistyorini Wulandari; Sinta Angeliya (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of this study is to examine the effect of understanding taxation, the tax system, and tax sanctions on tax evasion among taxpayers registered at KPP Pratama Cikarang Selatan. The research data was obtained by distributing questionnaires using the random sampling method. This study uses a quantitative approach, using primary data through a questionnaire. The population in this study were taxpayers registered at KPP Pratama Cikarang Selatan. And obtained as many as 95 respondents for analysis. The results of this study indicate that the taxation system has a positive effect on tax evasion. While understanding taxation and tax sanctions has no effect on tax evasion, Simultaneously, the understanding of taxation, the taxation system, and tax sanctions have no effect on tax evasion among taxpayers registered at KPP Pratama Cikarang Selatan.